The best compression ratio of modified piston for compressed natural gas(CNG)usage - Izar Farhan, Nor Khiri (2009)
Compression ratio can be defined as the pressure different between top dead center(TDC)and bottom dead center(BDC)of the piston in the combustion chamber.Compression ratio takes importance element to determine the power of the engine. Therefore,the objective of this study to determine the best compression ratio of modified piston for compressed natural gas(CNG)usage.The original engine is single cylinder four-stroke diesel engine.Compression ratio for this diesel engine is 20.28:1.The original piston of this engine is bore a bowl on the piston head to get certain compression ratio. Therefore,Computational Fluid Dynamics(CFD)method using FLUENT simulation software was used for this purpose.Model of combustion chamber with modified piston construct by using GAMBIT software,than export the model to FLUENT for dynamics analysis.The maximum pressure and maximum temperature in the combustion chamber model determined.Base on the simulation result,the highest pressure before the spark plug spark the flame is 15.5:1 of compression ratio.Meaning that,the best compression ratio of modified piston for compressed natural gas is 15.5:1.